2014
DOI: 10.1371/journal.ppat.1004234
|View full text |Cite
|
Sign up to set email alerts
|

A Repetitive DNA Element Regulates Expression of the Helicobacter pylori Sialic Acid Binding Adhesin by a Rheostat-like Mechanism

Abstract: During persistent infection, optimal expression of bacterial factors is required to match the ever-changing host environment. The gastric pathogen Helicobacter pylori has a large set of simple sequence repeats (SSR), which constitute contingency loci. Through a slipped strand mispairing mechanism, the SSRs generate heterogeneous populations that facilitate adaptation. Here, we present a model that explains, in molecular terms, how an intergenically located T-tract, via slipped strand mispairing, operates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 93 publications
4
36
1
1
Order By: Relevance
“…5A), which is in accordance with the SabA expression frequency described on European populations [11,31,49]. Importantly, SabA expression has been demonstrated to be subject to a dynamic on–off switching regulated by different genetic mechanisms, including slipped-strand mispairing (SSM) [11], a repetitive DNA element regulation by a rheostat-like mechanism [60], gene duplication by gene conversion [61], and by the acid-responsive signal (ArsRS) two component signal transduction regulatory system [62]. This rapid switch of SabA expression may explain the lack of association between SabA protein expression and sialyl-Le a and sialyl-Le x tissue levels (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…5A), which is in accordance with the SabA expression frequency described on European populations [11,31,49]. Importantly, SabA expression has been demonstrated to be subject to a dynamic on–off switching regulated by different genetic mechanisms, including slipped-strand mispairing (SSM) [11], a repetitive DNA element regulation by a rheostat-like mechanism [60], gene duplication by gene conversion [61], and by the acid-responsive signal (ArsRS) two component signal transduction regulatory system [62]. This rapid switch of SabA expression may explain the lack of association between SabA protein expression and sialyl-Le a and sialyl-Le x tissue levels (Fig.…”
Section: Discussionsupporting
confidence: 71%
“…Recent structural analysis has demonstrated that the basis for this functional diversity lies in two "diversity loops" within the carbohydrate binding site that represent areas of strong positive selection among babA sequences (13). Similarly, SabA shows polymorphism among clinical isolates in binding affinity to sialyl Lewis x (sLex) (31) and can be modulated by phase variation (32), gene conversion (33), and even variation in the length of a poly-T tract in the promoter region that serves as a rheostat-like mechanism to alter gene expression (34).…”
Section: Discussionmentioning
confidence: 99%
“…A dinucleotide cytosine-thymidine repeat in the 5= coding region allows for phase variation, which turns the expression of SabA on and off (18). A T-tract, located at the promoter region, controls sabA transcription initiation because the T-tract length influences binding of the RNA polymerase (45,46). Finally, the two-component signal transduction system ArsRS mediates the regulation of gene transcription by environmental changes.…”
Section: Discussionmentioning
confidence: 99%